Computer simulation of the thermoelectric heat flow sensor on the surface of the human body - Anatychuk, L.I.; Kobylianskyi , R.R.; Prybyla, A.V.; Konstantynovych, I.A.; Boychuk, V.V. (Journal of Thermoelectricity, 2022)
This paper presents the results of computer simulation of cyclic temperature effect on the human skin in dynamic mode. A three-dimensional computer model of the biological tissue has been built with regard to thermophysical processes, blood circulation, heat exchange, metabolic processes and the phase transition. As an example, the case is considered when on the skin surface there is a working tool the temperature of which changes cyclically according to a predetermined law in the temperature range [– 50 ÷ + 50] °C. Temperature distributions in different human skin layers in heating and cooling modes have been determined. The results obtained make it possible to predict the depth of the biological tissue freezing and heating under a given temperature effect.